Astyanax goyanensis (Miranda-Ribeiro, 1944), new combination and Astyanax courensis, new species (Ostariophysi: Characiformes): two Characidae from the upper rio Tocantins basin, Central Brazil - Bertaco,Vinicius A (2010)
Astyanax goyanensis (Miranda-Ribeiro, 1944), new combination, is redescribed based on the type series and topotypes, and A. courensis, new species, is herein described. Both species were collected in the rio dos Couros basin, upper rio Tocantins basin, Chapada dos Veadeiros, Goiás State, Brazil. These species possess the characters and general body morphology of the species of the Astyanax scabripinnis species complex. The new combination of Astyanax goyanensis is supported by the absence of characters that define Astyanacinus. Astyanax goyanensis and A. courensis differ from their congeners by meristic and morphometric characters, and color pattern. Astyanax goyanensis has only seven pelvic-fin rays, an uncommon character in the species of this genus, and A. courensis possesses only three or four scale rows below the lateral-line, fewer than typical of the genus.